Defects in nuclear structure and function promote dilated cardiomyopathy in lamin A/C–deficient mice - Nikolova, Vesna; Leimena, Christiana; McMahon, Aisling C.; Tan, Ju Chiat; Chandar, Suchitra; Jogia, Dilesh; Kesteven, Scott H.; Michalicek, Jan; Otway, Robyn; Verheyen, Fons; Rainer, Stephen; Stewart, Colin L.; et al. (The Journal of Clinical Investigation, 2004)
Laminopathies are a group of disorders caused by mutations in the LMNA gene that encodes the nuclear lamina proteins, lamin A and lamin C; their pathophysiological basis is unknown. We report that lamin A/C–deficient (Lmna–/–) mice develop rapidly progressive dilated cardiomyopathy (DCM) characterized by left ventricular (LV) dilation and reduced systolic contraction. Isolated Lmna–/– myocytes show reduced shortening with normal baseline and peak amplitude of Ca2+ transients. Lmna–/– LV myocyte nuclei have marked alterations of shape and size with central displacement and fragmentation of heterochromatin; these changes are present but less severe in left atrial nuclei. Electron microscopy of Lmna–/– cardiomyocytes shows disorganization and detachment of desmin filaments from the nuclear surface with progressive disruption of the cytoskeletal desmin network. Alterations in nuclear architecture are associated with defective nuclear function evidenced by decreased SREBP1 import, reduced PPARγ expression, and a lack of hypertrophic gene activation. These findings suggest a model in which the primary pathophysiological mechanism in Lmna–/– mice is defective force transmission resulting from disruption of lamin interactions with the muscle-specific desmin network and loss of cytoskeletal tension. Despite severe DCM, defects in nuclear function prevent Lmna–/– cardiomyocytes from developing compensatory hypertrophy and accelerate disease progression.